Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar Siswa pada Materi Jenis-Jenis Rangka Atap : Penelitian - Harefa, Widar Kristi Yanti; Harefa, Envilwan Berkat; Telaumbanua, Aprianus; Telaumbanua, Arisman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) model on students’ learning outcomes in the topic of Types of Roof Trusses at SMK Negeri 2 Gunungsitoli. The research background lies in the low student achievement scores, which were below the mastery criteria, and the learning process that was still dominated by lectures, making it less connected between theory and practice. This research employed an experimental method with a one-group pretest-posttest design. The instrument was validated using the Product Moment correlation and tested for reliability with Cronbach’s Alpha, both showing satisfactory results. Data analysis included prerequisite tests, correlation, simple linear regression, N-Gain analysis, and hypothesis testing. The findings revealed a significant improvement in learning outcomes after applying CTL, with a high level of effectiveness. CTL was proven to create contextual, interactive, and meaningful learning, fostering active student engagement and enhancing conceptual understanding. The results recommend CTL as an effective strategy for teaching technical subjects in vocational schools.